Imerslund-Grasbeck Syndrome: A Case Report - Ghosh, TN; Nayek, K; Banerjee, A (Journal of Nepal Paediatric Society, 2011)
Imerslund-Grasbeck syndrome is a rare autosomal recessive disorder due to selective malabsorption of Vitamin B12 at the level of cobalamin-intrinsic factor receptor mutation in the terminal ileum resulting in megaloblastic anaemia with proteinuria. Early detection of this rare disorder would enable screening and genetic counselling for asymptomatic family members. Key words: Imerslund Grasbeck Syndrome; Megaloblastic anaemia; Proteinuria DOI: http://dx.doi.org/10.3126/jnps.v31i3.5159 J Nep Paedtr Soc 2011;31(3): 249-250